2013
DOI: 10.4236/sgre.2013.43037
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Efficiency of Photogalvanic Cell for Solar Energy Conversion: Lissamine Green B-Ascorbic Acid-NaLS System

Abstract: Photogalvanic cells are photoelectrochemical cells chargeable in light for solar energy conversion and storage. They may be energy source for the future, if their electrical performance is increased. In this study, a photosensitizer Lissamine green B, a reductant Ascorbic acid and a surfactant NaLS have been used in the photogalvanic cell. The generated photopotential and photocurrent are 850.0 mV and 375.0 μA respectively. The conversion efficiency of the cell, fill factor and the cell performance were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the present work, the optimum cell performance in terms of electrical parameters is i max 6000 mA, i sc 3600 mA, V oc 1105 mV, P pp 822 mW, and CE 20.41%. The results in the present work are higher with respect to previous work 16,[27][28][29]37 and are also consistent with the aim of undertaking this work to further increase the electrical performance of PG cells. The results of the present study are sufficiently novel to report advancement over previous results (Table 9), viz., (a) P pp 649.6 mW, CE 8.12%, and power storage capacity 59 minutes, 37 (b) P pp 158.9 mW, V oc 960.0 mV, i sc 350.0 mA, and CE 1.52%, 27 (c) P pp 93.15 mW, V oc 919 mV, i sc 210 mA, and CE 0.8967%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present work, the optimum cell performance in terms of electrical parameters is i max 6000 mA, i sc 3600 mA, V oc 1105 mV, P pp 822 mW, and CE 20.41%. The results in the present work are higher with respect to previous work 16,[27][28][29]37 and are also consistent with the aim of undertaking this work to further increase the electrical performance of PG cells. The results of the present study are sufficiently novel to report advancement over previous results (Table 9), viz., (a) P pp 649.6 mW, CE 8.12%, and power storage capacity 59 minutes, 37 (b) P pp 158.9 mW, V oc 960.0 mV, i sc 350.0 mA, and CE 1.52%, 27 (c) P pp 93.15 mW, V oc 919 mV, i sc 210 mA, and CE 0.8967%.…”
Section: Discussionsupporting
confidence: 91%
“…28 A study on the photogalvanic effect in a lissamine green B sensitizer-ascorbic acid reductant-SLS system reported i sc 375 mA, V oc 850 mV, and CE 1.02%. 16 A study on the photogalvanic effect in an EDTA-safranine O-SLS system reported i sc 1700 mA, P pp 364.7 mW and CE 8.93%. 29 The present manuscript carries this work ahead and reports greater advancement over earlier reported work by employing the metanil yellow photo-sensitizer-formic acid couple in the presence of a cell performance enhancer surfactant at relatively high pH under articial and low illumination intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Chen, et al, 18 , In 2021, Koli et al, 19 reported outstanding work. Later on, Optimum results 24 , improved efficiency 25 and very similar work reported on TB (Toluidine B l u e ) 2 6 . G e n w a a n d S h r a d d h a 2 7 a n d i n order to performance [28][29][30] , and A numerous Photochemists [31][32][33][34] worked and also symmetrical results on photogalvanic [35][36] solar cells.…”
Section: Introductionmentioning
confidence: 52%
“…The problems encountered in the development of photogalvanic cells have been discussed from time to time. Krasnoholovets et al [17], Madhwani et al [18], Gangotri and Bhimwal [19], Genwa and Chauhan [20], Genwa and Singh [21], Rathode et al [22][23] and Yadav et al [24][25][26] have recently developed some photogalvanic systems for solar energy conversion and storage. The scientific community has successfully converted solar energy in electrical energy up to desired extent through various processes but storage capacity of solar energy is still not up to the mark to use it as and when required.…”
Section: Introductionmentioning
confidence: 99%